Forgotten DJ Stent with a Large Calculus at Its Distal End in an Ileal Conduit Diversion - Puri, Anurag (Hindawi Publishing Corporation, 2014)
Calculus formation in an ileal conduit following cystectomy is a known complication. Encrustation and formation of calculus may also occur over a DJ stent retained for a long period; but this is never reported in patients with conduit diversion because of close surveillance of these patients. Here we report first case of a large calculus encrusted over a forgotten DJ stent within an ileal conduit in a man who had undergone urinary diversion following radical cystectomy for carcinoma urinary bladder 8 years earlier.